RITUAL AGAMA DAN HARMONI SOSIAL KAUM URBAN: KAJIAN SOSIOLOGIS TERHADAP MUJAHADAH WARGA DI PERUM PANDANA MERDEKA NGALIYAN SEMARANG - Rahman, Luthfi; Pangasih, Sedya (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2020)
One of the Pandana Merdeka housing estates which has tried to instill harmony between communities with one another. One of the socializing activities of this housing is through mujahadah activities. This activity is very important to socialize in shaping the socio-religious aspects. The research method used is qualitative research using a sociological approach to religion. The results of this study indicate that Emile Durkheim's opinion regarding his observations about the religious phenomenon of Aboriginal groups in Australia is evident in the Pandana Merdeka housing community. This group phenomenon has the function of interacting with society in a moral order. As in the structure of the members of the Pandana Merdeka Housing community, each of them has a role in compiling the moral order through sacred ritual activities as collective action that reflects group solidarity.